2022
DOI: 10.3390/membranes12060621
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Enhanced Filtration and Dewatering of Kerosene

Abstract: Current approaches to dewatering aviation fuel such as kerosene are adsorption by activated charcoal, gravity separation, etc. The objective of this work is to develop and demonstrate the filtration and dewatering of kerosene using a carbon nanotube immobilised membrane (CNIM). Highly hydrophobic membranes were prepared by immobilising carbon nanotube (CNTs) over polytetrafluoroethylene (PTFE) and polyvinylidene difluoride (PVDF) microfiltration membrane for the dewatering of ppm level water from kerosene. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 38 publications
(71 reference statements)
2
18
0
Order By: Relevance
“…All three of these peaks are characteristic features of the CNTs and are observed in both samples. 64 Thermogravimetric analysis (TGA) was performed for the modified and unmodified samples using the PerkinElmer Pyris 7 TGA system 24,45,46,49 and is displayed in Figure S3. Thermogravimetric analysis (TGA) was performed to study the thermal stability of modified and unmodified samples.…”
Section: Membrane Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…All three of these peaks are characteristic features of the CNTs and are observed in both samples. 64 Thermogravimetric analysis (TGA) was performed for the modified and unmodified samples using the PerkinElmer Pyris 7 TGA system 24,45,46,49 and is displayed in Figure S3. Thermogravimetric analysis (TGA) was performed to study the thermal stability of modified and unmodified samples.…”
Section: Membrane Characterizationmentioning
confidence: 99%
“…33,34,66,67 Meanwhile the ethanol vapor passed through the membrane via activated diffusion over the CNT surface. 45,46 Here, the carbon nanotubes acted as a sorption site for the vapor molecules, particularly ethanol. 15,16,22,68−73 The temperature difference between the feed and permeate side acts as the driving force for the molecules to overcome diffusional resistance.…”
Section: Proposed Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The membrane is one of the most critical components in MD, since it has a direct impact on separation efficiency. , In organic recovery via MD, the membrane–solvent interaction plays an important role in permeation rate through membrane pores. Several modification methods have been reported to increase the partition coefficient of specific solvents through the membrane. We have used several nanocarbon morphologies in our membranes, including carbon nanotubes (CNTs), functionalized carbon nanotubes (f-CNTs), graphene oxide (GO), and reduced graphene oxide (r-GO). These have resulted in significant improvements in active diffusional transport as well as increased flux, selectivity, and mass transfer coefficients. We have also shown that integrating air sparging during sweep gas MD (AS–SGMD) synergistically enhances separation performance while contributing to improved antifouling behavior. , Air sparging is known to change the organic compound’s behavior at different temperatures, especially for high boiling solvents, and several studies have shown the removal of organics via air stripping at lower temperatures. The objective of this study was to investigate the potential of AS–SGMD in the enrichment of low-concentration aqueous isoprenol using different nanocarbon-immobilized membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Besides M-NPs and MO-NPs, nanocarbons [ 21 , 22 , 23 ] such as carbon nanotubes (CNTs) have also been used as antimicrobial agents [ 20 , 22 ]. CNTs are allotropes of carbon with great hydrophobicity and have been used in various other fields such as solvent enrichment [ 24 , 25 , 26 , 27 , 28 ], fouling reduction [ 29 , 30 ] and hydrocarbon dewatering [ 31 , 32 ]. Extensive research has been performed on CNTs to explore their antimicrobial properties [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%